The Revitalization Of Badrasanti’s Literary Work In The Form Of Musical Performances - Ochtaviani, Diana Elvira; Widodo, Widodo (Jurnal Seni Musik, 2021)
Badrasanti literary works are the literary works that have been revitalized into several art performances. From the result of observations, this is influenced by the times that are very enthusiastic about the cultural arts of the archipelago. This research aims to identify and describe the form of Kidung Puji Badrasanti’s show. The research approach that applied in this research is descriptive qualitative. The data collection techniques are conducted in a literature review, observation, interview, and documents study. The form of Kidung Puji Badrasanti’s show consists of aspects of composition and aspects of the presentation. The aspects of the composition consist of gendhing and balungan gendhing, rhythm, laya, laras, pathet, dynamics, and musical instruments in their appearance. The rhythm in the song of Puji Badrasanti uses dadi rhythm, laya in the Kidung Puji Badrasanti is nglentreh, laras in the song of Badrasanti’s praise is pelog, pathet that used is pathet lima, dynamics appear as needed. The musical instruments used are kemanak, kendhang ketipung and bem, slenthem, saron, peking, gong, kenong and kethuk. Aspects of the presentation pay attention to the players, the stage, makeup, fashion, lighting, and sound system.